Anisotropic Elasticity - Vannucci, Paolo (Lecture Notes in Applied and Computational Mechanics,, 2018)
This book presents a modern and unconventional introduction to anisotropy. The first part presents a general description of Anisotropic Elasticity theories while the second part focuses on the polar formalism: the theoretical bases and results are completely developed along with applications to design problems of laminated anisotropic structures. The book is based on lectures on anisotropy which have been held at Ecole Polytechnique in Paris.